THE REPRESENTATION OF SEMANTIC FEATURES OF INTERJECTION PHRASEOLOGICAL UNITS - Sabirova Dilshoda (Western European Studies, 2023)
This article is about structural peculiarities of Interjectional Phraseological Units and the models of forming new Interjectional Phraseological Units. This article is about semantic peculiarities of Interjectional phraseological units, according which there were found some special groups as benevolentness, evilness.
Keywords: Structure; Modal; Phraseological Nest